Mitochondrial Function and Dysfunction in Dilated Cardiomyopathy - Ramaccini, Daniela; Montoya-Uribe, Vanessa; Aan, Femke J.; Modesti, Lorenzo; Potes, Yaiza; Wieckowski, Mariusz R.; Krga, Irena; Glibetić, Marija; Pinton, Paolo; Giorgi, Carlotta; Matter, Michelle L. (Frontiers in Cell and Developmental Biology, 2021)
Cardiac tissue requires a persistent production of energy in order to exert its pumping function. Therefore, the maintenance of this function relies on mitochondria that represent the “powerhouse” of all cardiac activities. Mitochondria being one of the key players for the proper functioning of the mammalian heart suggests continual regulation and organization. Mitochondria adapt to cellular energy demands via fusion-fission events and, as a proof-reading ability, undergo mitophagy in cases of abnormalities. Ca2+ fluxes play a pivotal role in regulating all mitochondrial functions, including ATP production, metabolism, oxidative stress balance and apoptosis. Communication between mitochondria and others organelles, especially the sarcoplasmic reticulum is required for optimal function. Consequently, abnormal mitochondrial activity results in decreased energy production leading to pathological conditions. In this review, we will describe how mitochondrial function or dysfunction impacts cardiac activities and the development of cardiovascular disorders such as cardiomyopathies.